Replacement of performance enhancers by propolis ethanol extract in broiler diets - Vieira, Wesley Caetano; Geraldo, Adriano; Zangerônimo, Márcio Gilberto; Gonçalves, Jéssica Magela; Avelar, Guilherme Salviano; Costa, Lucas Marques Silva; Valentim, Jean Kaique; Garcia, Rodrigo Garófallo (Acta Scientiarum. Animal Sciences, 2021)
The present study was carried out to evaluate the substitution of synthetic performance enhancers by ethanolic propolis extract (EPE) in the diet of broilers and their effects on performance, carcass yield, noble cuts, viscera and bed quality. A completely randomized design was used, with four treatments and six replicates each, totaling 24 experimental plots with 20 birds each. The experimental treatments were: negative control, without the inclusion of performance improvement and EPE-free; positive control, containing avilamycin performance enhancer; Inclusion of 0.1% of EPE and; Inclusion of 0.2% EPE. The analyzed data were submitted to analysis of variance and applied the SNK test at 5% probability. There was no effect of the inclusion of additives on feed intake and feed conversion in the periods from 1 to 7, 1 to 21, and from 1 to 42 days of age. Weight gain was lower in birds receiving feed with the inclusion of 0.1% EPE in the period from 1 to 7 days, not differing from the other treatments in the other evaluation periods. Carcass characteristics, cuts, and viscera and bed moisture were not influenced by the treatments used. The inclusion of ethanol extract from propolis as a performance enhancer up to 42 days of age provided similar results to the use of performance enhancers based on avilamycin, thus being an efficient substitute in poultry production.